O impacto na arrecadação do ICMS da substituição tributária por carga líquida no Ceará: uma análise empírica do setor de alimentos com ênfase em bebidas no período 2007-2012 - Colaço, Maria do Socorro de Freitas (2014)
The establishment of this new mode of taxation was made, the ICMS Net change, through the Law No.14.237/2008, regulatedby Decree No.29.560/2008. The object of the research was to examine whether there was an increasein tax revenueby SEFAZ-EC after the Act which provides for the Cargo Net. Therefore,this study evaluated the effectiveness of this Law, for the period from 2007 to 2012, in the food sector with emphasis on beverages, using the difference in differences method. We have found evidence that the impact of the new mode of taxation in the food sectorwith an emphasis on beverages was positive, representing an increase of18.86%in revenues for the period 2007-2012.